Pembelajaran Bahasa Kedua yang Menyenangkan Menggunakan Metode Bermain Peran pada Siswa - Mahfud Nahrowi; Moh.Badiul Anis (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
This research aims to describe the learning of the second language that is pleasing physically and nonphysically after using the role-playing method in class II A MI NU Miftahul Huda 02 Karangmalang. The research method used in this study is descriptive, this form of research is a survey, the nature of this research is qualitative and this type of research is the Research Action Class (PTK) which in its implementation collaborate With class teachers. The subjects in this study were 1-grade teacher and 18 grade II students A. Pleasant Second Language learning using a role-playing method in class II A MI NU Miftahul Huda 02 Karangmalang increased from baseline by 19.59% to The II cycle became 76.95% increased by 57.36% with the